2014
DOI: 10.1111/jgs.12692
|View full text |Cite
|
Sign up to set email alerts
|

Delirium Risk Prediction, Healthcare Use and Mortality of Elderly Adults in the Emergency Department

Abstract: Background/Objectives Delirium is common and under-diagnosed in elderly Emergency Department (ED) patients. The primary aim of this study is to create a risk prediction rule for ED delirium. The secondary aim is to compare the mortality rates and resource utilization of delirious versus non-delirious elderly ED patients. Design Prospective observational study. Setting An urban tertiary care emergency department. Participants 700 patients 65 years of age or older and presenting for ED care. Measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
145
4
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(169 citation statements)
references
References 38 publications
13
145
4
7
Order By: Relevance
“…That study also found that the inability to perform activities of daily living (ADLs) was a risk factor for delirium; however, our ED did not routinely perform ADL screening. Prior studies have found that ED-diagnosed infections and ED-diagnosed intracranial haemorrhage22 increased the risk of delirium; in our study, ED delirium was only associated with an ED diagnosis of metabolic derangement. Francis et al 23 found that an abnormal sodium level and azotemia were risk factors for delirium, whereas Praditsuwan et al 12 found only pre-renal azotemia was associated with delirium.…”
Section: Discussionsupporting
confidence: 42%
“…That study also found that the inability to perform activities of daily living (ADLs) was a risk factor for delirium; however, our ED did not routinely perform ADL screening. Prior studies have found that ED-diagnosed infections and ED-diagnosed intracranial haemorrhage22 increased the risk of delirium; in our study, ED delirium was only associated with an ED diagnosis of metabolic derangement. Francis et al 23 found that an abnormal sodium level and azotemia were risk factors for delirium, whereas Praditsuwan et al 12 found only pre-renal azotemia was associated with delirium.…”
Section: Discussionsupporting
confidence: 42%
“…With regard to the total leukocyte count, Ansaloni et al (2010), De Castro et al (2014 and Kennedy et al (2014) concluded that the number of white cells is higher in patients with delirium (9.6 ± 4.3 vs. 8.3 ± 3.4), which corroborates the results obtained in this study.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, it has been shown that a short visit to the ED has repercussions on the cognitive status (recognised as delirium) of elderly patients. [22][23][24][25][26] Another hypothesis is that the presence of a potential overestimation of their function by the patients who had follow-up by phone (80%) rather than face-toface follow-up. However, this bias would be a nondifferential bias, so it would not advantage one group more than the other regarding the outcomes.…”
Section: Discussionmentioning
confidence: 99%